Cocrystallization of urea and succinic acid in "Nano-Crystallizer". (16th January 2021) - Yu, Qiushuo; Jia, Wanying; Pu, Jiaojiao; Wang, Yingchen; Yang, Huaiyu
Graphical abstract: Highlights: Nano-scale confinement alters ternary phase diagram and stability of cocrystals. Unstable U-SA 1:1 or stable 2:1 cocrystal products formed in different pore sizes. First-time producing U-SA 1:1 cocrystals by slow evaporation under confinement. In bulk solution only 2:1 cocrystals exist in an aqueous environment. Lower melting point of nano-cocrystals formed in smaller size of nano-crystallizer. Abstract: In the bulk scale of crystallization, urea-succinic acid (U-SA) cocrystals have been reported to only form stable 2:1 U-SA cocrystal, without any metastable 1:1 cocrystal, by slow evaporation and cooling crystallization in an aqueous solvent. In this work, cooling crystallization and evaporation crystallization were applied in nano-crystallizers, i.e. the nano-pores in controlled pore glass (CPG). It is the first time to demonstrate that, with confined solution, it is possible to produce and maintain metastable cocrystals during the slow crystallization process, indicating the strong influences of the confinement on the phase diagram and the thermodynamic properties of the nano-scale cocrystals. The influences of the urea and succinic acid concentration and the pore size of CPG on the polymorphs and melting point of the nanocrystal have been investigated. Further understanding of the mechanism may contribute to new methods for maintaining the unstable materials and discovering new forms of pharmaceutical compounds and materials.